Rancang Bangun Sistem Informasi Manajemen Pada Koze Patisserie di Kota Batam - Leony, Alvina; Tukino, Tukino (LPPM Universitas Putera Batam, 2024)
As technology continues to develop and improve in leaps and bounds, there is an inevitable high demand for more technology-based systems (in the form of websites, software, applications, or even web-based applications) to manage tasks in businesses with greater efficiency, accuracy, and speed. Every business, whether a small personally owned store or a large conglomerate, needs to keep up and compete in this rapidly developing world. One such business is Koze Patisserie, a patisserie shop that requires a management information system to help manage and keep track of their products, orders, ingredients, customers, suppliers, and more automatically. This article will use the SDLC Waterfall method, consisting of the following steps: requirement analysis, system design, implementation (coding), integration and testing, deployment, and maintenance, to develop the application using Visual Basic as its programming language in the integrated development environment (IDE) Visual Studio and Microsoft Access as its database to store all relevant data records